Synthesis, inhibitory activity and in silico docking of dual COX/5-LOX inhibitors with quinone and resorcinol core - Sisa, Miroslav; Dvorakova, Marcela; Temml, Veronika; Jarosova, Veronika; Vanek, Tomas; Landa, Premysl (European journal of medicinal chemistry, 2020)
Based on the significant anti-inflammatory activity of natural quinone primin (5a), series of 1,4-benzoquinones, hydroquinones, and related resorcinols were designed, synthesized, characterized and tested for their ability to inhibit the activity of cyclooxygenase (COX-1 and COX-2) and 5-lipoxygenase (5-LOX) enzymes. Structural modifications resulted in the identification of two compounds 5b (2-methoxy-6-undecyl-1,4-benzoquinone) and 6b (2-methoxy-6-undecyl-1,4-hydroquinone) as potent dual COX/5-LOX inhibitors. The IC50 values evaluated in vitro using enzymatic assay were for compound 5b IC50 = 1.07, 0.57, and 0.34 μM and for compound 6b IC50 = 1.07, 0.55, and 0.28 μM for COX-1, COX-2, and 5-LOX enzyme, respectively. In addition, compound 6d was identified as the most potent 5-LOX inhibitor (IC50 = 0.14 μM; reference inhibitor zileuton IC50 = 0.66 μM) from the tested compounds while its inhibitory potential against COX enzymes (IC50 = 2.65 and 2.71 μM for COX-1 and COX-2, respectively) was comparable with the reference inhibitor ibuprofen (IC50 = 4.50 and 2.46 μM, respectively). The most important structural modification leading to increased inhibitory activity towards both COXs and 5-LOX was the elongation of alkyl chain in position 6 from 5 to 11 carbons. Moreover, the monoacetylation in ortho position of bromo-hydroquinone 13 led to the discovery of potent (IC50 = 0.17 μM) 5-LOX inhibitor 17 (2-bromo-6-methoxy-1,4-benzoquinone) while bromination stabilized the hydroquinone form. Docking analysis revealed the interaction of compounds with Tyr355 and Arg120 in the catalytic site of COX enzymes, while the hydrophobic parts of the molecules filled the hydrophobic substrate channel leading up to Tyr385. In the allosteric catalytic site of 5-LOX, compounds bound to Tyr142 and formed aromatic interactions with Arg138. Taken together, we identified optimal alkyl chain length for dual COX/5-LOX inhibition and investigated other structural modifications influencing COX and 5-LOX inhibitory activity.
Keywords: Cyclooxygenase Inhibitors; Anti-inflammatory activity; simulace molekulového dockingu; Computer Simulation; Quinones; počítačová simulace; Oxidation-Reduction; Molecular Docking Simulation; spektrální analýza; vztahy mezi strukturou a aktivitou; Benzoquinones; 5-Lipoxygenase; Catalytic Domain; Cyclooxygenase; oxidace-redukce; Spectrum Analysis; benzochinony; Lipoxygenase Inhibitors; inhibitory lipoxygenas; inhibitory cyklooxygenasy; resorcinoly; katalytická doména; Resorcinols; Structure-Activity Relationship